The Diversity in the Genus Canis Challenges Conservation Biology: A Review of Available Data on Asian Wolves - Werhahn, Geraldine; Senn, Helen; Macdonald, David W.; Sillero-Zubiri, Claudio (Frontiers in Ecology and Evolution, 2022)
Taxa belonging to the Genus Canis can challenge taxonomists because species boundaries and distribution ranges are often gradual. Species delineation within Canis is currently not based on consistent criteria, and is hampered by geographical bias and lack of taxonomic research. But a consistent taxonomy is critical, given its importance for assigning legal protection, conservation priorities, and financial resources. We carried out a qualitative review of the major wolf lineages so far identified from Asia wolf lineages described for Asia from historical to contemporary time and considered relevant morphological, ecological, and genetic evidence. We present full mitochondrial phylogenies and genetic distances between these lineages. This review aims to clarify summarize the available data on contemporary Asian wolf lineages within the context of the larger phylogenetic Canis group and to work towards a taxonomy that is consistent within the Canidae. We found support for the presence and taxon eligibility of Holarctic grey, Himalayan/Tibetan, Indian, and Arabian wolves in Asia and recommend their recognition at the taxonomic levels consistent within the group.